PREVALENCE OF OBESITY AMONG THE ADULT POPULATION OF TAJIKISTAN - S.M. ABDULLOZODA (Avicenna Tajik State Medical University, 2022)
Objective: To provide the national estimates of the prevalence of adult obesity (OB) in the Republic of Tajikistan according to official statistics in the 2015-2019 period. Methods: OB prevalence among the adult population of the Republic of Tajikistan in the 2015-2019 period was estimated based on the annual reports of the Center for Statistics under the President of the Republic of Tajikistan. The epidemiological analysis included an assessment of the OB prevalence across the studied period, distribution of overweight people by gender and region of residence. Results: The OB prevalence among the adult population between 2015 and 2019 ranged from 25 to 57 cases per 100,000 people, with an increase by 128% across this period. In 2016 the prevalence increased by 23.1%, in 2017 - by 16.7%, in 2018 - by 10.7% and in 2019 - by 43.5%. The highest prevalence of OB was noted among the residents of the capital; during the study period its increase was 69.2% (from 104 to 176 per 100,000 people; p<0.001). The second high OB prevalence was found in the Sughd region, where it showed an increase across the studied period by 186.7%; in 2019 it was 86 per 100,000 compared to 30 per 100,000 in 2015 (p<0.001). The lowest OB prevalence was noted among the residents of GBAO, where it ranged from 3 to 11 cases per 100,000 people (p>0.05). The same trend was observed among the residents of the Khatlon region, where in the study period the increase in the OB prevalence was insignificant (from 6 to 19 per 100,000 people; p>0.05). Analysis of the data showed that during this period, the life expectancy among women increased by 128.2%, among men - by 150%. However, among the males in the 2016-2018 period there was no significant increase in the OB prevalence (p>0.05). People aged 45 years and above had significantly higher OB prevalence than all other age groups (p<0.001) during the study period. Only in 2016 there was no significant increase (p>0.05) of the OB prevalence among the elderly population (75 and above). Conclusion: The analysis of the data obtained showed that in the Republic of Tajikistan, the OB prevalence among the adult population in the study period ranged from 25 to 75 cases per 100,000 people and increased by 128% between 2015 and 2019. Primary health care facilities should develop a national registry of obese people and provide clinical and epidemiological monitoring of the overweight population. Promoting a healthy lifestyle, healthy diet and physical exercise of the population through the media will improve the health level and quality of life of the population.